The greatest showman [videorecording (DVD)] - Jackman, Hugh; Williams, Michelle, 1980-; Efron, Zac (Twentieth Century Fox Home Entertainment, 2018)
An original musical screenplay brings to life the story of P.T. Barnum and his creation of "the greatest show on Earth". Rising from nothing, P.T. sets out to make a better life for his family. His creativity and drive take him on an fantastic journey beyond what he or anyone else could have imagined. In the end he creates a magical experience that will be enjoyed and celebrated by generations to come.